Quercetin Inhibits Pyroptosis in Diabetic Cardiomyopathy through the Nrf2 Pathway - Zhang Wei; Zhou Jing; Kang Pinfang; Shi Chao; Qian Shaohuan (Journal of Diabetes Research)
The present study investigated whether quercetin promotes the nuclear translocation of nuclear factor erythroid-2-related factor 2 (Nrf2) to inhibit pyroptosis progression and ameliorate diabetic cardiomyopathy. We evaluated the protective effects of quercetin against diabetic cardiomyopathy by analyzing the expression of pyroptosis pathway proteins, myocardial cell apoptosis rate, degree of myocardial fibrosis, and serum inflammatory indices in the hearts of model rats with diabetes. We evaluated the expression of Nrf2 in the nucleus of cardiomyocytes and H9C2 cells to clarify the role of quercetin in promoting the nuclear translocation of Nrf2. In addition, we coincubated cardiomyocytes with the Nrf2 inhibitor ML385 to confirm that quercetin inhibits the diabetes-induced cardiomyocyte pyroptosis via the Nrf2 pathway. We found that quercetin promoted the nuclear translocation of Nrf2 in cardiac cells of diabetic rats, increased the expression of the antioxidant proteins HO-1, GCLC, and SOD, reduced the accumulation of ROS and the degree of cardiomyocyte apoptosis, and alleviated diabetes-induced cardiac fibrosis. The therapeutic effects of quercetin were further validated in H9C2 cardiomyocytes. Interestingly, ML385 prevented the beneficial effects of quercetin on diabetic cardiomyopathy, further indicating that the quercetin-mediated inhibition of pyroptosis requires the participation of the Nrf2 pathway. In conclusion, quercetin promoted the nuclear translocation of Nrf2, increased the expression of antioxidant factors in cells, and inhibited the progression of cell pyroptosis, thereby alleviating diabetic cardiomyopathy.